Determination of Radiation Absorbed Dose to Primary Liver Tumors and Normal Liver Tissue Using Post-Radioembolization 90Y PET - Srinivas, Shyam M.; Natarajan, Navin; Kuroiwa, Joshua; Gallagher, Sean; Nasr, Elie; Shah, Shetal N.; DiFilippo, Frank P.; Obuchowski, Nancy; Bazerbashi, Bana; Yu, Naichang; McLennan, Gordon (Frontiers in Oncology, 2014)
Background: Radioembolization with Yttrium-90 (90Y) microspheres is becoming a more widely used transcatheter treatment for unresectable hepatocellular carcinoma (HCC). Using post-treatment 90Y PET/CT scans,the distribution of microspheres within the liver can be determined and quantitatively assessesed . We studied the radiation dose of 90Y delivered to liver and treated tumors. Methods: This retrospective study of 56 patients with HCC, including analysis of 98 liver tumors, measured and correlated the dose of radiation delivered to liver tumors and normal liver tissue using glass microspheres (TheraSpheres®) to the frequency of complications with mRECIST. 90Y PET/CT and triphasic liver CT scans were used to contour treated tumor and normal liver regions and determine their respective activity concentrations. An absorbed dose factor was used to convert the measured activity concentration (Bq/mL) to an absorbed dose (Gy). Results: The 98 studied tumors received a mean dose of 169 Gy (mode 90-120 Gy;range 0-570 Gy). Tumor response by mRECIST criteria was performed for 48 tumors that had follow up scans. There were 21 responders (mean dose 215 Gy) and 27 nonresponders (mean dose 167 Gy). The association between mean tumor absorbed dose and response suggests a trend but did not reach statistical significance (p=0.099). Normal liver tissue received a mean dose of 67 Gy (mode 60-70 Gy; range 10-120 Gy). There was a statistically significant association between absorbed dose to normal liver and the presence of two or more severe complications (p=0.036). Conclusion: Our cohort of patients showed a possible dose response trend for the tumors. Collateral dose to normal liver is nontrivial and can have clinical implications. These methods help us understand whether patient adverse events, treatment success, or treatment failure can be attributed to the dose which the tumor or normal liver received.